Analisis Kepuasan Konsumen dalam Pembelian Tanaman Hias pada Sentra Usaha Tanaman Hias di Kota Bogor - SALSABILA KAUTSAR; I G.A.A. LIES ANGGRENI; NI WAYAN PUTU ARTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Analysis Customer Satisfaction in Buying Ornamental Plants at Ornamental Plant Business Center in Bogor City Nowadays, needs are not only limited to primary needs (clothing, food, and shelter) but also secondary needs, such as entertainment. Everyone's entertainment needs are different, one of which is by buying ornamental plants. Buying, caring for and cultivating ornamental plants can make someone feel happy. This study aims to determine the characteristics of consumers, the level of customer satisfaction as well as the level of performance and importance of the ornamental plant business centers in the city of Bogor, one of which is the ornamental plant business center on Jl. Dadali. The data used are primary data by distributing questionnaires to 50 respondents who are consumers of ornamental plant business centers. The data taken are qualitative and quantitative using primary and secondary data. The analysis used is descriptive analysis, Customer Satisfaction Index (CSI) and Important Performance Analysis (IPA). The results of this study indicate that the level of consumer satisfaction in purchasing ornamental plants at the ornamental plant business center on Jl. Dadali is in the satisfied category with a percentage of 64.69%. And based on the performance and importance gumesius diagram, quadrant I needs to be improved again, namely marketing communication, comfort of the place as well as cleanliness and tidiness of the place.